2022
DOI: 10.1002/fsn3.2876
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the variations in physicochemical characteristics of squab meat during the braising cooking process

Abstract: Braised squabs are traditional Chinese foods. However, the processing is highly experience dependent and lacks a theoretical basis. Hence, a comparative study of the physicochemical properties in different processing stages of braised squabs was necessary. We observed the physicochemical changes in the processing stages of braised squabs (raw meat, braised meat, and fried meat). The color parameters, moisture content, and drip loss rate gradually decreased during the processing. On the contrary, crude protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…This result is consistent with previously reported works. For instance, Zhao et al [ 24 ] also pointed out that the diameter of muscle fiber significantly increased in the braised meat. Compared with fresh beef muscle fiber, fewer connective tissue or muscle fiber membranes can be observed on the microstructure of beef muscle fiber after stewing for 120 or 150 min.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with previously reported works. For instance, Zhao et al [ 24 ] also pointed out that the diameter of muscle fiber significantly increased in the braised meat. Compared with fresh beef muscle fiber, fewer connective tissue or muscle fiber membranes can be observed on the microstructure of beef muscle fiber after stewing for 120 or 150 min.…”
Section: Resultsmentioning
confidence: 99%
“…During the breeding and selling of squabs, body weight serves as the primary quality inspection standard, because it is closely linked to the postnatal growth and development of the squabs [ 17 ]. Extensive research has demonstrated that the gut microbiota plays a crucial role in animal growth and development [ 18 ], and FMT can effectively regulate animal growth and development [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than 111 million pairs of breeding pigeons have been produced and 1.6 billion squabs have been sold in China in recent years ( Gao, 2022 ). Despite this, the total squab production in China has dropped from 80% of the global production because squab sales in the United States, Canada, Great Britain, and France are also increasing quickly ( Kokoszyński et al, 2020 ; Gao, 2022 ; Ji et al, 2022 ; Zhao et al, 2022 ; Zhong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%